Anemia in Bolivian children: a comparative analysis among three regions of different altitudes. Issue 1 (18th March 2019) - Cordero, Dilberth; Aguilar, Ana Maria; Casanovas, Carmen; Vargas, Elizabeth; Lutter, Chessa K.
Abstract: Here, we analyzed four population‐based demographic and health surveys conducted in Bolivia between 1998 and 2016 to understand trends in anemia in children from 6 to 59 months of age by selected sociodemographic characteristics and three categories of altitude: low, medium, and high. Over the 18‐year period, the prevalence of anemia was virtually unchanged while that in children living at high altitude increased. Anemia in children living at all three altitude categories is more than 40% and a severe public health problem according to the World Health Organization. We did not identify a single consistent risk factor for anemia in children living at high altitude compared with those living at medium or low altitude. The most consistent characteristic associated with childhood anemia across the three altitude categories was diarrhea in the last 2 weeks. Low length/height for age, an adolescent or anemic mother, a mother with no or little education, and a mother who speaks Quechua or Aymara were also risk factors. We conclude that it is necessary to review anemia policies and programs and prioritize children who are at greatest risk of developing anemia, particularly those living at high altitude. As iron deficiency appears to explain only a small part of childhood anemia, there is also a need to better understand its other causes and develop appropriate interventions. Abstract : Here, we analyzed four population‐based demographic and health surveys conducted in Bolivia between 1998 and 2016 to understand trends in anemia in children from 6 to 59 months of age by selected sociodemographic characteristics and three categories of altitude: low, medium, and high.